STUDY OF THE PHYSICO-CHEMICAL PARAMETERS CHARACTERIZING THE QUALITY OF EL’MENIA LAKE. ALGERIA - Benbitour1, S; Babaamer2, Z (university of eloued -جامعة الوادي, 2019)
The objective of this work is to evaluate the physico-chemical quality of El-Menia Lake, experiencing the effect of the discharges of waste water in this lake. The results of physico-chemical study show that El-Menia Lake is characterized by a high conductivity and very hard quality with remarkable pollution in most points. Concerning the concentrations of heavy metal elements we found a high concentration in some metals like the lead, cadmium, cobalt and some metals less than standard value of surface water
article
Keywords: El-Menia Lake, physico-chemical analysis, heavy metals.